Paisagem histórica urbana: contributos da cartografia para caracterização da evolução e identidade urbanas da freguesia de Paranhos (Porto) - Carvalho, Mariana Raquel Salino (CEM – Cultura, Espaço & Memória, 2021)
Cities, as the place where the daily life happens, are in constant mutation and construction, and so they are a testimonial of Humanity’s past and present ways of living and aspirations. Therefore, we should see them as a manifestation of cultural heritage and an element of the community’s identity that is always being threaten by its own fast transformation. The in-depth knowledge of each city’s urban stratigraphy becomes essential in order to find the most appropriate solutions for the promotion of sustainable urban development and preserve the intrinsic characteristics of the area. A comparative analysis of cartographic sources, that register the morphology of the city in different moments, allows to understand a stratigraphy of that territory, to identify the problems in its urban mesh and to detect the most relevant elements of its development and morphology